2018
DOI: 10.1177/0741932518781946
|View full text |Cite
|
Sign up to set email alerts
|

Family Quality of Life and Partnership for Families of Students With Deaf-Blindness

Abstract: Family–professional partnerships are a key support for families of children with disabilities, but little is known about families of children with deaf-blindness. This study examined (a) the factor structures of the Beach Center on Disability Family–Professional Partnership and Family Quality of Life (FQOL) Scales utilizing a national sample of families of children and youth with deaf-blindness (age birth to 22 years), and (b) the relationship between family–professional partnership and FQOL at the subdomain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…of the time management skills required for success. The study results were consistent with those of White ( 2014) (Kyzar et al, (2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…of the time management skills required for success. The study results were consistent with those of White ( 2014) (Kyzar et al, (2018).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the study confirmed the validity of the first hypothesis of the study, as it proved the effectiveness of the family counseling program in improving the meaning of life for deaf-blind children, as the results confirmed the existence of statistically significant differences between the average of the previous and subsequent measurements of the experimental group on the meaning of life scale of deaf-blind children in favor of the dimensional scale. The results of the study agree with those of: Frederickson and Turner (2003), Kyzar (2010), Gaspar et al (2017), (Kyzar et al, 2018), Wolsey (2017), Sayed (2015), Ezzat (2010)and Abdul Hafith (2008). Many studies have found the effectiveness of a training program to develop daily life skills for the deaf-blind children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Boehm et al [84] investigate the relationship between the parents' religiosity and the improvement of the FQoL. In the demographic aspects category (c2), nine articles consider as predictive variables for FQoL the following factors: the age of the child with a disability [41,80,83,85], the gender of the child [24,39,82], the type of disability [31,80,84], the degree of disability [80,81], the number of siblings [58,81], and the marital status of the parents [44].…”
Section: Main Results On Fqol In the 0-to 6-year Stagementioning
confidence: 99%
“…The majority of the studies consulted in scientific literature examined the relationships between life satisfaction, parental self-efficacy, well-being, and coping strategies predominantly in the parents of children with sensory impairments. Widespread literature reports that protective and risk factors positively or negatively influence the quality of life in families with deaf or blind children, deaf-blind children, or children with other developmental disabilities [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Among the protective factors, several scholars assume the coexistence of psychological and situational variables: parental resilience, optimism, hope orientation, adaptability and meaning-focused coping with stress, good communication skills with sensory disabled children, marital satisfaction, and social support from formal and informal networks [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%